Antioxidant Activity of Stem, Fruit, and Leaf Extracts of Sonneratia ovata Mangrove Using the DPPH Method - Ikhlasul Amal; Muhammad Hendri; Muhammad Yosi Prasetyo; Mohammad , Javad Hessami (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Mangrove plants are a type of plant that is able to grow in brackish waters in different salinity conditions in the tropics so as to form a unique and distinctive ecosystem. One of the mangrove plants that live in Indonesian waters is the mangrove of the Sonneratia genus. Empirically, parts of the mangrove plant of the Sonneratia sp. species such as fruit, bark, and leaves have been widely used as traditional medicine by the community to treat various diseases and can be used as natural antioxidants that are good for the body. The purpose of this study was to determine and analyze the potential activity of antioxidant compounds from the stem, fruit, and leaf extract of mangrove S. ovata. The antioxidant activity test method used the DPPH method which was measured by the percentage of inhibition and IC₅₀ value. The results of antioxidant activity from several test concentrations of stem, fruit, and leaf extracts obtained a very high percentage of inhibition so that the antioxidant compounds contained in the three samples could reduce free radical activity. Fruit samples had the highest antioxidant potential with an IC₅₀ value of 4.59 ppm, followed by leaf samples at 25.39 ppm and stem samples at 45.91 ppm. Thus, mangroves of the S. ovata species have the potential as natural antioxidants that are good for the body and only require <50 ppm to reduce free radicals by 50%.